Allergic contact cheilitis due to lipstick - Yatty Ravitasari; Desiana Radithia; Priyo Hadi (Universitas Airlangga, 2015)
Background: Cheilitis is a common problem of unknown etiology. A possible cause of cheilitis is contact allergy. Drugs, lipsticks, sunblock and toothpaste are the most common implicated allergens. Allergic contact cheilitis is a chronic superficial inflammatory disorder of the vermilion borders characterized by desquamation due to delayed-type hypersensitivity reaction. Purpose: We report a management of Allergic contact cheilitis due to lipsticks. Case: A 21-year-old woman had a history of atopic allergy to eggs, milk, and chicken presented with sore, dry, fissured, scaled and sometimes bleeding lip, over a 3-month period after application of a lipstick. Her symptoms persisted despite treatments with hydrocortisone cream. The patient provided a detailed history and underwent physical examination and patch tests to cosmetic components and patch test to her own lipstick. The patient had strongly-positive result to the tested lipstick. A diagnosis of allergic contact cheilitis was made based on the history and clinical findings. Case management: Patient was advised to avoid wearing lipstick. To relieve symptoms, treatment was initiated with combined topical corticosteroid, antibiotic, and moisturizer. Conclusion: Contact allergy patients should be tested for both cosmetic component series and their own lipsticks to exclude exfolliative cheilitis, infection, or light actinic cheilitis as causal agents.